Deficiency of MMP17/MT4-MMP Proteolytic Activity Predisposes to Aortic Aneurysm in Mice - Martín Alonso, Mara; García Redondo, Ana B.; Guo, Dongchuan; Camafeita, Emilio; Martínez, Fernando; Alfranca, Arántzazu; Méndez Barbero, Nerea; Pollán, Ángela; Sánchez Camacho, Cristina; Denhardt, David T.; Seiki, Motoharu; Vázquez, Jesús; et al. (My University, 2015)
Rationale:Aortic dissection or rupture resulting from aneurysm causes 1% to 2% of deaths in developed countries. These disorders are associated with mutations in genes that affect vascular smooth muscle cell differentiation and contractility or extracellular matrix composition and assembly. However, as many as 75% of patients with a family history of aortic aneurysms do not have an identified genetic syndrome. Objective:To determine the role of the protease MMP17/MT4-MMP in the arterial wall and its possible relevance in human aortic pathology. Methods and Results:Screening of patients with inherited thoracic aortic aneurysms and dissections identified a missense mutation (R373H) in the MMP17 gene that prevented the expression of the protease in human transfected cells. Using a loss-of-function genetic mouse model, we demonstrated that the lack of Mmp17 resulted in the presence of dysfunctional vascular smooth muscle cells and altered extracellular matrix in the vessel wall; and it led to increased susceptibility to angiotensin-II¿induced thoracic aortic aneurysm. We also showed that Mmp17-mediated osteopontin cleavage regulated vascular smooth muscle cell maturation via c-Jun N-terminal kinase signaling during aorta wall development. Some features of the arterial phenotype were prevented by re-expression of catalytically active Mmp17 or the N-terminal osteopontin fragment in Mmp17-null neonates. Conclusions:Mmp17 proteolytic activity regulates vascular smooth muscle cell phenotype in the arterial vessel wall, and its absence predisposes to thoracic aortic aneurysm in mice. The rescue of part of the vessel-wall phenotype by a lentiviral strategy opens avenues for therapeutic intervention in these life-threatening disorders. Key Words: aorta ¿ aneurysm ¿ cardiovascular diseases ¿ matrix metalloproteinases ¿ matrix metalloproteinase 17 ¿ osteopontin
Keywords: aorta ¿ aneurysm ¿ cardiovascular diseases ¿ matrix metalloproteinases ¿ matrix metalloproteinase 17 ¿ osteopontin